Operation state assessment of wind power system based on PSO + AHP—FCE - Zhang, Jing; Bai, Jing; Zhang, Zhiqiang; Feng, Weidong (Frontiers in Energy Research, 2022)
Aiming at the disadvantage of strong subjectivity in determining the weight of analytic hierarchy process combined with fuzzy comprehensive evaluation method(AHP-FCE) in the comprehensive evaluation of wind power system operation state, this thesis proposes an analytic hierarchy process(AHP) based on particle swarm optimization (PSO) and constructs a analytic hierarchy process combined with particle swarm optimization algorithm(PSO + AHP) model to optimize the weight. It can overcome the disadvantage that can’t improve the weight value and consistency once the judgment matrix is given in the AHP-FCE method. This approach results in a weight value with a relatively high degree of consistency. Secondly, aiming at the serious deviation of multiple evaluation indexes in the sub-project level at the same time, this thesis introduces the deterioration index, and applies the fuzzy comprehensive evaluation method to establish the operation state evaluation model of the wind power system; Finally, based on the actual monitoring data of a wind farm over a period of time, its operational status was evaluated using the proposed PSO-AHP based with FCE. The results show that compared with the traditional AHP-FCE evaluation method, the evaluation results of the proposed method are relatively good. It has practical value and guiding significance to improve the real-time reliability of wind turbine grid-connected operation, optimize the unit maintenance strategy and reduce the cost of wind power generation.